Gregor the Overlander - Collins, Suzanne (New York : Scholastic, 2003)
When eleven-year-old Gregor and his two-year-old sister are pulled into a strange underground world, they trigger an epic battle involving men, bats, rats, cockroaches, and spiders while on a quest foretold by ancient prophecy.
Sequel: Gregor and the prophecy of Bane.
Keywords: Brothers and sisters -- Fiction; Animals -- Fiction; Missing persons -- Fiction; Fantasy